Interfacial polarisation on gallium arsenide membranes - Prodromakis,T; Konstantinidis,G; Papavassiliou,C; Toumazou,C (Micro & Nano Letters, IET, 2010)
An investigation on the dielectric properties of gallium arsenide membranes is presented. Particularly, the authors exploit the interfacial polarisation effect of microstrip and coplanar transmission lines on multilayered membrane structures. Such structures are in favour with the Maxwell-Wagner polarisation, which can be used for resembling the dielectric characteristics of high-k materials. The authors demonstrate a technique for attaining large slowing factors while the corresponding dielectric losses are significantly reduced.